Scoping Review: Self Care Instrument for Chronic Kidney Disease Patients on Hemodialysis - Firah Azzahra; Wahyu Hidayati; Sri Padma Sari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic kidney disease (CKD) is an incurable global health problem, with a growing prevalence, particularly in Asia. It is estimated that by 2030, 2.16 million individuals will require hemodialysis, a 233% increase from previous years. Self-care practices are an important aspect in improving health, preventing complications, and supporting daily functioning and well-being of patients. Therefore, a valid and reliable instrument is needed to measure the level of self-care in patients with chronic diseases. Objective to identify a validated self-care assessment instrument for hemodialysis patients. The methodological approach refers to Arksey and O'Malley, with article searches through ScienceDirect, PubMed, and EBSCO databases using relevant keywords, focusing on full-text, English-language, open access, and published in the last 18 years published between 2007 and 2024, keywords included